Numerical Study on the Effect of Dual Electron Transport Layer in Improving the Performance of Perovskite–Perovskite Tandem Solar Cells. Issue 3 (2nd January 2023) - Kumar, Dinesh; Bansal, Nitin Kumar; Dixit, Himanshu; Kulkarni, Ashish; Singh, Trilok
Abstract: C Perovskite–perovskite tandem solar cells (P‐TSCs) are an attractive option to overcome the limitation of Si‐based solar cells due to their ability to deposit in both the top and bottom cells by a simple solution process. Despite these advantages, the power conversion efficiency (PCE) of P‐TSCs still falls behind that of Si‐perovskite tandem devices and is highly limited by the nonradiative recombination between the perovskite and electron transport layer (ETL) interface. In this work, with the help of numerical simulations (SCAPS 1D), the influence of the various ETLs on the performance of P‐TSCs is studied. Different ETLs such as C60, PCBM, ZnO, WO3, CdSe, and In2 O3, BCP are incoroprated, which directly interface with the perovskite absorber layer in top (high bandgap absorber layer) and bottom subcell (low bandgap absorber layer) of P‐TSC. The simulation analysis shows that reducing the interface surface defect density and band offsets at the ETL/perovskite interface significantly helps achieving high‐efficiency P‐TSC over 35% . Various remediation for incorporating present simulation analysis into practical devices for better‐performing P‐TSCs is also provided. The analysis provides a pathway toward understanding the reasons behind the current trend of low PCE in 2 terminal P‐TSC and achieving high‐efficiency P‐TSC solar cells. Abstract : The influence of the various electron transporting layers on the performance of perovskite–perovskite tandem solar cells shows that interfacial defects density and band offset plays an important role in the device efficiency and stability.